Kajian Kinerja Industri Kecil Dengan Metode Balance Score Card Dan Analytical Hierarchy Process - MT Safirin (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Small industry is one important component in national economic structure, because it can absorb a lot of manpower and a lot of exploiting the potential of natural resources abundant in Indonesia. The number of small industries in Indonesia is quite a lot, but has not been matched by much higher performance. Therefore the number of small industries which are so muchslower average growth and is difficult to compete with large industrial products and imported products. Industry performance is one of the criteria used to measure industry growth. With performance measurement-performance small industry and handicraft villages can be foundin different areas of industry map homeland. During the performance measurement industry is based only on financial aspects. Performance measurement of the financial aspect is important, but still there are other aspects that are also important and need attention because theyaffect the performance of the industry, namely: aspects of customer (market), internal business processes and learning and growth. Therefore it is necessary for measuring the performance of various aspects of small scale industries so that their performance can be evaluated and formulated a model maintenance and development of small industries and handicraft villages are more comprehensive. The method used is the Balanced Scorecard (BSC) and Analytical Hierarchy Process (AHP). The Balanced Scorecard measures the performance of the business / industry with 4 perspective, financial, customer, business process within the company, and the process of learning and growth. Method of Analytical Hierarchy Process (AHP) is used to embobot each perspective and each Critical Success Factor. Research results showed that the average performance of small industries in Trowulan Pasuruan Stone Statue of 2083 (category enough). There are 2 perspectives of a very large weight on the performance of a stone statue of a small industry of financial and customer. Moderate success factors have great influence on both perspectives is the total asset turn over the tattoo and the number of new customers.